Cerebellar-Cortical Connectivity Is Linked to Social Cognition Trans-Diagnostically - Brady, Roscoe O.; Beermann, Adam; Nye, Madelaine; Eack, Shaun M.; Mesholam-Gately, Raquelle; Keshavan, Matcheri S.; Lewandowski, Kathryn E. (Frontiers in Psychiatry, 2020)
Background: Psychotic disorders are characterized by impairment in social cognitive processing, which is associated with poorer community functioning. However, the neural mechanisms of social impairment in psychosis remain unclear. Social impairment is a hallmark of other psychiatric illnesses as well, including autism spectrum disorders (ASD), and the nature and degree of social cognitive impairments across psychotic disorders and ASD are similar, suggesting that mechanisms that are known to underpin social impairments in ASD may also play a role in the impairments seen in psychosis. Specifically, in both humans and animal models of ASD, a cerebellar-parietal network has been identified that is directly related to social cognition and social functioning. In this study we examined social cognition and resting-state brain connectivity in a people with psychosis and in neurotypical adults. We hypothesized that social cognition would be most strongly associated with cerebellar-parietal connectivity, even when using a whole-brain data driven approach. Methods: We examined associations between brain connectivity and social cognition in a trans-diagnostic sample of people with psychosis (n=81) and neurotypical controls (n=45). Social cognition was assessed using the social cognition domain score of the MATRICS Consensus Cognitive Battery. We used a multivariate pattern analysis to correlate social cognition with resting-state functional connectivity at the individual voxel level. Results: This approach identified a circuit between right cerebellar crus I,II and left parietal cortex as the strongest correlate of social cognitive performance. This connectivity-cognition result was observed in both people with psychotic disorders and in neurotypical adults. Conclusions: Using a data-driven whole brain approach we identified a cerebellar-parietal circuit that was robustly associated with social cognitive ability, consistent with findings from people with ASD and animal models. These findings suggest that this circuit may be marker of social cognitive impairment trans-diagnostically and support cerebellar-parietal connectivity as a potential therapeutic target for enhancing social cognition.